Being on hemodialysis during the COVID‐19 outbreak: A mixed‐methods' study exploring the impacts on dialysis adequacy, analytical data, and patients' experiences. Issue 1 (16th September 2020) - Sousa, Helena; Ribeiro, Oscar; Costa, Elísio; Frontini, Roberta; Paúl, Constança; Amado, Leonilde; Miranda, Vasco; Ribeiro, Fernando; Figueiredo, Daniela
Abstract: For individuals with end‐stage renal disease (ESRD), the novel coronavirus can present several additional challenges in disease self‐management. This study aimed to explore the impacts of the COVID‐19 pandemic in non‐COVID‐19 patients with ESRD undergoing in‐center hemodialysis (HD). A mixed‐methods study was conducted with a purposive sample recruited from one dialysis unit in Portugal. Quantitative data were collected retrospectively from patients' medical records from February 2020 (T1—before the outbreak) and from April 2020 (T2—during lockdown). Semi‐structured interviews were conducted with 20 patients (66.9 ± 11.9 years old) undergoing HD for an average of 46.1 months (±39.5) in April 2020. Overall results suggested that dialysis adequacy and serum albumin levels decreased significantly at T2, while phosphorus levels increased. The findings from thematic analysis suggested several psychosocial negative impacts and impacts on disease and treatment‐related health behaviors (eg, difficulties managing dietary restrictions during the lockdown and diminished physical activity), which can partially explain these quantitative results. However, some patients were also able to find positive impacts in this experience and problem‐focused and emotional strategies were identified to cope with the demands of COVID‐19. Several recommendations have been made to mitigate patients' emotional, relational, and educational unmet needs during the current pandemic and in the event of new outbreaks.